2019
DOI: 10.21276/ap.2019.8.2.23
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of Cactus

Abstract: Xerophytes are the great fighters due to their amazing abilities to deal with extremely challenging environment. These plants are distinct from other mesophytes in having morphological, anatomical and physiological adaptations. Due to these adaptive modifications the biochemistry of these plants is also unique and they are the vital source of valuable phytochemical contents of a range of uses, especially medicinal utilization. Cactus is one of the most widely distributed plants in the xeric environment and has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…This may be due to its significant antioxidant effects shown in the study and its protective effect on the antioxidant enzymes CAT and SOD. In addition, previous studies had reported the anti-inflammatory effect of the plant extracts as Chandra et al. (2019) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to its significant antioxidant effects shown in the study and its protective effect on the antioxidant enzymes CAT and SOD. In addition, previous studies had reported the anti-inflammatory effect of the plant extracts as Chandra et al. (2019) .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to its significant antioxidant effects shown in the study and its protective effect on the antioxidant enzymes CAT and SOD. In addition, previous studies had reported the anti-inflammatory effect of the plant extracts as Chandra et al (2019). The anti-amyloid effect of some plants was previously evaluated as a therapeutic modality for AD as Ginkgo biloba which showed an anti-amyloid aggregation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Os frutos da palma apresentam pesos variáveis (50 a 150g) em função da espécie, das condições climáticas de cada região de cultivo ou país de origem (CHANDRA et al, 2019). Estes possuem uma baga de formato oval e alongada, um pericarpo muito espesso e quando atinge o seu ponto ótimo de maturação apresenta características sensoriais agradáveis como polpa suave, suculenta, gelatinosa, aveludada, açucarada, de odor muito apreciado, sobretudo devido ao conteúdo de pectina e de compostos mucilaginosos, além de possuir um amplo espetro de cores (branca-esverdeada, amarela, laranja, vermelho e roxa) (SAPATA et al, 2017).…”
Section: Introductionunclassified